CSC425: Introduction to Computer Programming / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2022)
The course is intended to introduce students to the steps in problem solving. Student will study the basic concepts of structured programming to understand the software development and programming process. The aim is to produce students who understand the fundamental ideas of computer programming and algorithms and able to implement the problem solution using C++ programming language.